2008
DOI: 10.1530/eje-07-0145
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of obesity

Abstract: More than half of the European population are overweight (body mass index (BMI) O25 and !30 kg/m 2 ) and up to 30% are obese (BMIR30 kg/m 2 ). Being overweight and obesity are becoming endemic, particularly because of increasing nourishment and a decrease in physical exercise. Insulin resistance, type 2 diabetes, dyslipidemia, hypertension, cholelithiasis, certain forms of cancer, steatosis hepatis, gastroesophageal reflux, obstructive sleep apnea, degenerative joint disease, gout, lower back pain, and polycys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0
23

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(171 citation statements)
references
References 131 publications
4
141
0
23
Order By: Relevance
“…Therefore, bariatric surgery should only be advocated to morbidly obese individuals after careful evaluation of the risk-tobenefit ratio. According to the current National Institute of Health clinical recommendations, surgical A c c e p t e d M a n u s c r i p t treatment of obesity should be considered when BMI is greater than 40 or greater than 35 in patients with a high-risk obesity-related condition following failure of other treatments for weight control (reviewed by Bult et al, 2008) . Results from an uncontrolled study assessing the effect of bariatric surgery in morbidly obese women with PCOS also reported sustained weight loss and complete resolution of all features defining PCOS, including hirsutism, hyperandrogenism, menstrual irregularity, anovulation, IR and metabolic abnormalities (Escobar-Morreale et al, 2005).…”
Section: Bariatric Surgery In the Treatment Of Pcos Related Obesitymentioning
confidence: 99%
“…Therefore, bariatric surgery should only be advocated to morbidly obese individuals after careful evaluation of the risk-tobenefit ratio. According to the current National Institute of Health clinical recommendations, surgical A c c e p t e d M a n u s c r i p t treatment of obesity should be considered when BMI is greater than 40 or greater than 35 in patients with a high-risk obesity-related condition following failure of other treatments for weight control (reviewed by Bult et al, 2008) . Results from an uncontrolled study assessing the effect of bariatric surgery in morbidly obese women with PCOS also reported sustained weight loss and complete resolution of all features defining PCOS, including hirsutism, hyperandrogenism, menstrual irregularity, anovulation, IR and metabolic abnormalities (Escobar-Morreale et al, 2005).…”
Section: Bariatric Surgery In the Treatment Of Pcos Related Obesitymentioning
confidence: 99%
“…For this purpose, we analyzed the urine samples of obese patients by high-resolution proton NMR ( 1 H NMR) spectroscopy in combination with multivariate statistics. Furthermore, we investigated the obese metabolic phenotype (metabotype) changes in relation to two different bariatric surgery procedures (biliopancreatic diversion and Roux-en-Y gastric bypass) 9,10 that are detailed in the Supplementary Information.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of obesity treatment is weight loss, which leads to reduced insulin resistance, better control of diabetes mellitus, lower blood pressure, an improved lipid profile and, consequently, reduced risk of cardiovascular disease 2 . Studies have shown disappointing results for the conservative treatment of obesity in the long term, while there is evidence in the literature that surgical treatment of obesity can lead to more sustainable weight loss in selected patients 3 . Although there have been accurate indications and satisfactory results, there are considerable complications when obese or overweight patients are submitted to surgery, with incisional hernias being one of the most common delayed complications 4,8 .…”
Section: Introductionmentioning
confidence: 99%